2008
DOI: 10.12973/ejmste/75347
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Attitudes Toward Computer Use in Slovakia

Abstract: ICT has a very short history in Slovakia. A majority of Slovak schools accessed computers and internet only after 2000. Different financial support and schools' participation in various projects resulted in non-random distribution of computers across Slovakian elementary schools. We examined whether 1) attitudes toward computers could be affected by the accessibility of computers at schools and 2) how the use of computers between school and home environment differ. Attitudes toward ICT were positive and gender… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 15 publications
(14 reference statements)
2
17
1
Order By: Relevance
“…The findings of the present study revealed that Iranian students' CALL attitude was positive in general which is in full agreement with previous studies such as Fančovičová and Prokop (2008), Kilic (2001), and Sanders and Morrison-Shetlar (2001). This finding supports the fact that the ubiquity of technology in the 21 st century resulted in positive perceptions towards using computers in teaching and learning of any subject in general and foreign languages in particular.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The findings of the present study revealed that Iranian students' CALL attitude was positive in general which is in full agreement with previous studies such as Fančovičová and Prokop (2008), Kilic (2001), and Sanders and Morrison-Shetlar (2001). This finding supports the fact that the ubiquity of technology in the 21 st century resulted in positive perceptions towards using computers in teaching and learning of any subject in general and foreign languages in particular.…”
Section: Discussionsupporting
confidence: 93%
“…Particularly, it was found that both the degree of exhibition and effectiveness of CALL vs. non CALL were higher among university students in comparison to junior high-school and high-school students. It may account that university students are not only more computer literate and have less computer anxiety (Fančovičová & Prokop, 2008), but also they perceive the value of using computers in their academic tasks, since they are more exposed to technology and have more opportunities to use computers for course-related activities (Hong, Ridzuan, & Kuek, 2003). As the previous studies indicate, digital gender divide is closing and today's female students are becoming more experienced in computer use (Lin & Yu, 2008) and thus they take advantage of the technology according to their needs and preferences (Poynton, 2005) as they become more educated.…”
Section: Discussionmentioning
confidence: 99%
“…This finding, that boys enjoy ICT more than girls, however, is not consistent with the reviewed literature (Adebowale et al, 2009;Busch, 1995;Fančovičová & Prokop 2008;Kaino, 2008;Ogan et al, 2005;Shashaani, 1993;Teo, 2008). We believe that a factor explaining differences in these studies and our results may actually reflect differences in ages in the samples studied and differences in the use of computers in schools and at home.…”
Section: Attitudes In the Use Of Ictcontrasting
confidence: 85%
“…High anxiety in girls, as reported by Baloğlu and Çevik (2008), Kaino (2008), Adebowale et al (2009), andKubiatko et al (2011), and girls' low self-confidence, as reported by Volman and Van Eck (2001), Ogan et al (2005), or Christoph et al (2015), may contribute to a low achievement of digitals skills. On the other hand, enjoyment seems to be similar for both genders, according to Ogan et al (2005), Fančovičová and Prokop (2008), Kaino (2008), Teo (2008), and Adebowale et al (2009) but higher in girls than in boys at early ages (Kubiatko et al, 2011). We believe it is relevant to know whether this is also the situation of the Catalan students at the beginning of secondary education or not and to consider taking advantage of this enjoyment to develop more entertaining and effective ICT activities.…”
Section: Figure 1 Percentage Of Females (In Dark Grey) and Males (Inmentioning
confidence: 93%
See 1 more Smart Citation